Moderate and Non-Moderate Discursive Tendencies in Kitab Kuning - Iswahyudi Iswahyudi; Galih Akbar Prabowo; Fitri Annas Sholihah (Perkumpulan Alumni dan Santri Mahyajatul Qurro', 2025)
Pesantren and their Kitab Kuning tradition are widely framed as pillars of religious moderation in Indonesia, yet this dominant narrative often overlooks the internal diversity and ambivalence of classical juridical and theological discourses. This study critically reexamines the assumption that Kitab Kuning teaching uniformly produces moderate Islam by analyzing how moderate and non-moderate statements coexist within authoritative texts and how their vocabularies and epistemological orientations shape interpretations in plural societies. Using qualitative content analysis, the authors reviewed a corpus of widely used pesantren editions and purposively selected classical works that explicitly contain statements on tolerance, exclusion, and delegitimization, focusing on Fath al-Mu‘in, I‘ānat al-Thalibin, al-Majmu‘ Sharh al-Muhadhdhab, Sharh Sahih Muslim, and Kifayat al-Akhyar (with complementary reference to other texts). Textual segments were coded as “moderate” when they acknowledged legitimate plurality or used inclusive legal language, and as “non-moderate” when they employed categorical delegitimation (e.g., heresy or unbelief). The interpretation was then situated within historical and epistemological frames (bayani, ‘irfani, burhani) and reread for contemporary relevance. Results show two recurring and systematic patterns: inclusive-juridical markers such as qala fulan/qila, khilafan, qaulani, wajh/aujuh that normalize disagreement and epistemic openness, and exclusionary markers such as bid‘ah qabihah/munkarah, ahl al-dalalah, la yashihhu, and kufr that invalidate practices or groups (including intra-madhhab and inter-madhhab exclusions and condemnations of certain ritual innovations and beliefs). Exclusionary judgments appeared predominantly in strongly bayani-oriented fiqh and theological formulations, whereas pluralizing vocabularies were more frequent in ‘irfani or burhani tendencies. The findings imply that moderation in pesantren is not inherent in Kitab Kuning but emerges through selective, critical, and contextual reading. Religious moderation programs should therefore strengthen critical hermeneutics and reader responsibility. The study is limited by selective sampling and does not comprehensively map socio-political contestations.